Depression severity and psychosocial determinants of physical activity behavior in in-patients with major depressive disorders. (November 2022) - Cody, Robyn; Beck, Johannes; Brand, Serge; Donath, Lars; Eckert, Anne; Faude, Oliver; Hatzinger, Martin; Holsboer-Trachsler, Edith; Imboden, Christian; Kreppke, Jan-Niklas; Lang, Undine E.; Ludyga, Sebastian; et al.
Abstract: Background: Physical inactivity is a world-wide health issue. In people with major depressive disorders approximately 68% do not reach the recommended physical activity levels. Psychosocial determinants of and implicit attitudes towards physical activity serve to explain physical activity behavior and may form the basis of interventions to promote physical activity. The aim of this study was to examine, whether psychosocial determinants and implicit attitudes towards physical activity vary according to depression severity. Methods: Physically inactive, adult in-patients diagnosed with major depressive disorder (according to ICD-10) were recruited from four Swiss psychiatric clinics. Psychosocial determinants of physical activity were assessed with seven questionnaires pertaining to motivational and volitional aspects of physical activity. Implicit attitudes towards physical activity were measured with a computer-based Single Target Implicit Association Test. Results: In-patients ( N = 215, M age = 41 ± 13 years, 53% female) with major depressive disorder reporting more severe ( n = 52) depression symptomology exhibited less favorable psychosocial determinants for physical activity behavior (self-efficacy, negative outcome expectancies, intention, intrinsic motivation, introjected motivation, external motivation, action planning, perceived barriers, coping planning) compared to those with mild ( n = 89) and moderate ( n = 74) depression symptomology. Positive outcome expectancies, identified, social support and implicit attitudes towards physical activity did not vary according to depression severity. Conclusions: Psychosocial determinants of physical activity do vary according to depression severity. Attempts to promote physical activity among people with major depressive disorder should take depression severity into account when developing and delivering interventions. Trial registration: ISRCTN registry, ISRCTN10469580, registered on 3 rd September 2018, https://www.isrctn.com/ISRCTN10469580 . Highlights: Depression severity may be associated with physical activity determinants, explaining physical activity behavior. More severe depression symptoms were associated with less favorable psychosocial determinants. More severe depression symptoms were not associated with implicit attitudes towards physical activity. Depression severity may need to be considered when designing interventions.